ART THERAPY TO REDUCE DEPRESSION DUE TO DOMESTIC VIOLENCE AT “X” COMMUNITY IN AMBON - Violenta Soukotta; Monty P. Satiadarma (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2018)
This research is aimed to the practice of Art Therapy to reduce Depression due to Domestic Violence of “X” Community in Ambon. Individuals undergoing domestic violence are at high risk of having many negative psychological impacts. One of its impact is depression. Individuals with depression due to domestic violence need to get a social support and psychotherapy. Art Therapy is one  of a form of psychotherapy that can be suggested to treat depressed individuals. This study used qualitative research method and was conducted from April 22nd 2017 to May 22nd 2017. The participants in this study were three women who had been undergoing domestic violence for some years. The result of  this study showed that art therapy had reduced the level of depression of  the three participants. Art therapy hass affected participants in these areas: (a) gaining self-knowledge, (b) medium of catharsis and relaxation, (c) expression of emotions and feelings, (d) facilitating self development, (e) stimulating self awareness, (f) enhancing self confidence through the success of creating the art works, (g) reducing stress and boredom. The therapeutic relations bonded between the participants and researcher might also have  affected participants through their feelings of being helped and receiving deep concern from others.Penelitian ini bertujuan untuk mempraktekkan  Terapi Seni demi  mengurangi Depresi akibat Kekerasan Dalam Rumah Tangga pada Komunitas "X" di Ambon. Individu yang mengalami kekerasan dalam rumah tangga memiliki resiko tinggi mengalami banyak dampak psikologis negatif. Salah satu dampaknya adalah depresi. Individu yang mengalami depresi akibat kekerasan dalam rumah tangga perlu mendapatkan dukungan sosial dan psikoterapi. Terapi seni adalah salah satu bentuk psikoterapi yang dapat disarankan untuk mengobati individu yang mengalami depresi. Penelitian ini menggunakan metode penelitian kualitatif dan dilakukan mulai tanggal 22 April 2017 sampai dengan 22 Mei 2017. Partisipan dalam penelitian ini adalah tiga (3) wanita yang telah mengalami kekerasan dalam rumah tangga selama beberapa tahun. Hasil penelitian ini menunjukkan bahwa terapi seni telah mengurangi tingkat depresi pada tiga partisipan tersebut. Terapi seni telah mempengaruhi partisipan pada area berikut: (a) mendapatkan pengertian diri, (b) media katarsis dan relaksasi, (c) ekspresi emosi dan perasaan, (d) memfasilitasi pengembangan diri, (e) merangsang kesadaran diri, (f) meningkatkan kepercayaan diri melalui keberhasilan menciptakan karya seni, (g) mengurangi stres dan kebosanan. Hubungan terapeutik yang dijalin antara peserta dan peneliti mungkin juga telah mempengaruhi partisipan melalui perasaan tertolong dan menerima perhatian mendalam dari orang lain